Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

4x + 12 = -7y
-y + 12 = 4x
Solve with elimination


Sagot :

Take the second equation and flip it around so the y on the left ends up on the right and the 4x on the right ends up on the left.  This makes all negatives positive and all positives negative.   -4x   + 12  = y 

Then add the first equation to the second equation 
4x   +12   = -7y
-4x   + 12  =   this eliminates the x's
          24 = - 6y            then divide by - 6
           - 6     - 6
         - 4    = y

So if you know that y = negative 4, you can substitute into either equation.  I pick the second one because I am a lazy person.  
  -y  + 12  = 4 x
-(-4) + 12 = 4 x     combine your numbers
     16      = 4 x        then divide by 4
       4      =  x
So your solution is: x = 4 and y = -4 or this is also written (4, -4)

Does that work for you?
Lilith
[tex]\begin{cases}4x + 12 = -7y \\ -y + 12 = 4x \end{cases} \\ \\\begin{cases}4x + 7y = -12 \\ -4x-y =-12 \end{cases} \\+ ------- \\6y=-24\ \ /:6\\ \\y=-\frac{24}{6}\\ \\y=-4[/tex]

[tex]4x+12=-7y\\ \\ 4x+12=-7*(-4)\\ \\4x=28-12\\ \\4x=16\ \ /:4\\ \\x=\frac{16}{4}\\ \\ x=4 \\ \\ \begin{cases}x=4 \\ y=-4 \end{cases}[/tex]


We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.